Infection of polarized bovine respiratory epithelial cells by bovine viral diarrhea virus (BVDV). Issue 1 (31st December 2021) - Su, Ang; Fu, Yuguang; Meens, Jochen; Yang, Wei; Meng, Fandan; Herrler, Georg; Becher, Paul
ABSTRACT: Bovine viral diarrhea virus (BVDV) is affecting cattle populations all over the world causing acute disease, immunosuppressive effects, respiratory diseases, gastrointestinal, and reproductive failure in cattle. The virus is taken up via the oronasal route and infection of epithelial and immune cells contributes to the dissemination of the virus throughout the body. However, it is not known how the virus gets across the barrier of epithelial cells encountered in the airways. Here, we analyzed the infection of polarized primary bovine airway epithelial cells (BAEC). Infection of BAEC by a non-cytopathogenic BVDV was possible via both the apical and the basolateral plasma membrane, but the infection was most efficient when the virus was applied to the basolateral plasma membrane. Irrespective of the site of infection, BVDV was efficiently released to the apical site, while only minor amounts of virus were detected in the basal medium. This indicates that the respiratory epithelium can release large amounts of BVDV to the environment and susceptible animals via respiratory fluids and aerosols, but BVDV cannot cross the airway epithelial cells to infect subepithelial cells and establish systemic infection. Further experiments showed that the receptor, bovine CD46, for BVDV is expressed predominantly on the apical membrane domain of the polarized epithelial cells. In a CD46 blocking experiment, the addition of an antibody directed against CD46 almost completely inhibited apical infection, whereas basolateral infection was not affected. While CD46 serves as a receptor for apical infection of BAEC by BVDV, the receptor for basolateral infection remains to be elucidated.